The Problem of Plastic Waste, A Comparison of the Systems in Indonesia and the Netherlands: The Urgency of State Intervention and Legal Instruments - Mahardika, Septilia; Pratamo, Nathanael Bayu Ajie (ECOTON: Ecological Observation and Wetlands Conservation, 2024)
The trading phenomenon of plastic waste from the Global North to the Global South has caused environmental issues due to the production and import of poorly managed plastic waste in the recipient countries. This research aims to compare the existing plastic waste management systems in Indonesia and the Netherlands and to examine state intervention and legal instruments in place. Data is analyzed qualitatively by comparing and discussing the juridical and socio-political aspects descriptively, thus highlighting the complexity of the plastic waste issue and the importance of interventions to renew plastic waste management, taking examples from Global North countries like the Netherlands. The Netherlands implements a circular economy scheme with the concept of extended producer responsibility, banning single-use plastics, mandating labeling on plastic products, promoting waste sorting, and increasing public awareness. Through these steps, Indonesia is expected to improve waste management towards environmental sustainability and gradually reduce plastic waste imports.